Effect of shod walking on plantar pressure with varying uphill gradients - Sen, Suranjana; Bhattacharyya, Debojyoti; Chaterjee, Subhojit; Kumar, Bhuvnesh; Pal, Madhusudan (Asian Journal of Medical Sciences, 2020)
Background: Uphill walking is biomechanically stressful. Changes in plantar pressure, is one of the important predictors of this stress and increased risk of foot injuries. It has been reported that civilians as well as different occupational workers have to walk over uphill gradient with footwear which may cause changes in plantar pressure. Till date published data on plantar pressure is not available of Indian population during shod walking with uphill gradients. Aims and Objective: The present study was aimed to generation of data base on plantar pressure and find out the effect of shod walking (wearing occupational boot) on plantar pressure at different uphill gradients. Materials and Methods: Twenty healthy male participated in this study. Plantar pressure was recorded using the pressure measurement system during walking at 4 km/hr speed on treadmill at level and different uphill gradients. Results: It was observed that the PP at all the five regions of both right and left foot (Forefoot, Mid-foot, Medial, Lateral, Heel and Overall) increased gradually along with the increase in gradients. There was significant increase of 8.94%, 9.93%, 18.22%, 16.06%, 10.27%, 12.92% respectively at left forefoot, mid-foot, heel, medial, lateral and overall regions at 10% gradient compared to level walking. Similarly, in right foot the increase was observed 8.20%, 10.82%, 14.28%, 13.75%, 8.27%, 10.88% in respective foot regions compared to level walking. Conclusion: Observations of the present study stated that with increasing gradient plantar pressure at various foot regions increased in both feet in comparison to level walking, maximum plantar pressure observed in heel region in both feet in comparison to other studied regions. This data will be considered as normal planter pressure value of adults at level and uphill gradients shod walking and may be utilized for prognosis of foot disorders and efficacy of treatment modalities of population comparable with studied individuals (for similar age, height and weight).